A new insight on the mechanisms of filling closed carbon nanotubes with molten metal iodides. (December 2016) - Nie, Chunyang; Galibert, Anne-Marie; Soula, Brigitte; Flahaut, Emmanuel; Sloan, Jeremy; Monthioux, Marc
Abstract: Filling double-walled carbon nanotubes with iodine and various metal iodides (metals, alkali metals and transition metals) by the molten phase method was performed and the influence of possibly relevant chemical and physical properties of the filling materials on the filling rate was investigated. It was found, within the metal iodides series, that the filling rate can be mainly related to the redox potential (EMIx/M ) of the filling material. Other parameters such as the possible formation of dimers, surface tension, or the early release of iodine may also play an additional role in the filling process.